A GIS based interpretation of the historical evolution of urban settlements in Mangalore City, India - Dhanaraj, K.; Angadi, Dasharatha P. (Spatial information research (Online), 2021)
The fact that the present state of evolution of settlement in a city is most often composed of remnants it’s past, superimposed and juxtaposed together with the new developments. This can be used to gain new insights on spatial history and dynamism of settlements evolution and also for spatial information approximation for historical narrative in general. This study attempts to trace and visualise the evolution and the spatial pattern of urban settlement distribution in Mangalore using GPS locations of historical buildings and structures from 600 AD. to 1970 AD. The study employs GIS and spatial statistical techniques such as spatial mean centre, standard distance, standard deviational ellipse, Average Nearest Neighbour, Kernel density and variable buffer model. It was found from the study that historical buildings and structures including temples and churches are closely associated with the evolution and distribution settlement in Mangalore. The study also substantiates the historical fact that the eventual intensification concentration of settlements in the current urban centre was largely influenced by colonial settlers. The temporal fluctuation of spatial mean centre of the city was also found in Mangalore.